High-elasticity polyethylene foaming composite material and preparation method thereof

By adding modified nanosilicon nitride and modified graphene to the polyethylene foam composite material, the material formulation is optimized and modern nanotechnology is combined to solve the shortcomings of polyethylene foam composite material in terms of resilience and thermal stability, and a high-performance polyethylene foam composite material is achieved, suitable for high-performance applications.

CN119798823AInactive Publication Date: 2025-04-11NINGBO JIUHE NEW MATERIAL CO LTD

Patent Information

Application Number
CN202510077817.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polyethylene foam composites have shortcomings in terms of resilience and thermal stability, and it is difficult to meet the needs of high-performance applications, especially in the automotive industry, aerospace and sports equipment.

Method used

By optimizing the material formula of highly elastic polyethylene foam composite materials, combined with modern nanotechnology, modified nanosilicon nitride and modified graphene, the modified nanosilicon nitride is modified by hydrogen bond cross-linking, and the modified graphene is uniformly dispersed in low-density polyethylene by introducing epoxy groups, synergistically improving the material's rebound performance and thermal stability.

Benefits of technology

It significantly improves the resilience and thermal stability of polyethylene foam composite materials, so that it can maintain good resilience under long-term high-load working, and is suitable for high-performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798823A_ABST
    Figure CN119798823A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of foamed composite materials, in particular to a high-elasticity polyethylene foamed composite material and a preparation method thereof, and the high-elasticity polyethylene foamed composite material comprises the following raw materials: low-density polyethylene, modified nano silicon nitride, modified graphene, azodicarbonamide, a coupling agent, an antioxidant, an antistatic agent and a plasticizer. The low-density polyethylene, the modified nano silicon nitride and the modified graphene play a role through a synergistic effect, the low-density polyethylene provides a stable carrier supporting effect for the modified nano silicon nitride and the modified graphene, and the modified nano silicon nitride increases the cohesive force of a low-density polyethylene matrix, so that the heat resistance of the modified nano silicon nitride is improved; the modified graphene optimizes the molecular chain structure of polyethylene, and the stress dispersion capability of the foamed composite material is enhanced through the two-dimensional structure and the ultrahigh specific surface area of the modified graphene, so that the rebound resilience of the material is synergistically improved; and the polyethylene foaming composite material can still keep good rebound resilience under long-time high-load work.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foamed composite materials, in particular to a high-elastic polyethylene foamed composite material and a preparation method thereof. Background Art

[0002] Polyethylene is one of the most common plastic materials. It has good molding processability, excellent chemical resistance, insulation and low cost. It is widely used in packaging, construction, automobiles and electronics. In particular, low-density polyethylene has good flexibility and scalability, and is suitable for applications that require high flexibility. However, traditional low-density polyethylene materials still have limitations during use. They perform poorly under large loads, lack sufficient strength and stiffness, and are prone to permanent deformation. By combining the polyethylene matrix with a foaming agent such as azodicarbonamide, the material can have good elasticity and cushioning while maintaining a low density. The foaming process can not only reduce the weight of the material, but also give the material better resilience, cushioning and impact resistance. It is particularly suitable for packaging, automotive interiors, sports equipment and other fields. However, the polyethylene foam composite materials currently on the market are still insufficient in terms of resilience and thermal stability, and it is difficult to meet the needs of high-performance applications. In order to broaden market applications, especially in the automotive industry, aerospace, sports equipment and packaging materials, the material is required to have good resilience and high temperature resistance and other characteristics to meet the market's growing demand for high-performance and environmentally friendly materials. It is very meaningful to develop a high-elastic polyethylene foam composite material. Summary of the invention

[0003] (1) Technical issues to be solved

[0004] The purpose of the present invention is to provide a high-elastic polyethylene foam composite material and a preparation method thereof, by optimizing the material formula of the high-elastic polyethylene foam composite material, and combining modern nanotechnology to significantly improve the resilience of the polyethylene foam composite material, a polyethylene foam composite material with high elasticity and high strength performance is prepared, and its market application range is expanded.

[0005] (2) Technical solution

[0006] To achieve the above object, on the one hand, the present invention provides a high elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 70-80 parts of low density polyethylene, 2-5 parts of modified graphene, 2-4 parts of azodicarbonamide, 0.5-1 part of coupling agent, 0.5-1 part of antioxidant, 0.1-0.5 part of antistatic agent, and 1-3 parts of plasticizer;

[0007] The high elastic polyethylene foam composite material also includes:

[0008] Modified nano silicon nitride;

[0009] The modified nano silicon nitride and low-density polyethylene are in a weight ratio of 5: (70-80);

[0010] The modified nano silicon nitride is prepared by hydrogen bonding and cross-linking modification of nano silicon nitride, and the particle size of the modified nano silicon nitride is 50 to 80 nm, and the specific surface area is 90 to 120 m 2 / g.

[0011] Furthermore, the preparation method of the modified nano silicon nitride comprises:

[0012] S11. The nano silicon nitride powder is dissolved in anhydrous ethanol under stirring, and then ultrasonically treated at an ultrasonic frequency of 40 to 50 kHz for 0.5 to 1 h at room temperature to obtain a first mixed solution;

[0013] S12. The first mixed solution was subjected to high-speed centrifugation at a speed of 6000 to 8000 rpm for 10 to 15 min. The separated solid was washed three times with anhydrous ethanol and then vacuum dried at a drying temperature of 50 to 60 ° C. After drying for 12 to 14 h, the nano-silicon nitride intermediate was ground into a powder for standby use;

[0014] S13. Dissolve N-(3-aminopropyl)-3-chloropropyltrimethoxysilane in anhydrous ethanol under stirring, slowly add 0.1 mol / L sodium hydroxide solution after stirring for 0.5 to 1 h, and continue stirring for 2 to 3 h to obtain a second mixed solution;

[0015] S14. The nano silicon nitride intermediate powder is dissolved in the second mixed solution under stirring, the reaction temperature is set to 65 to 75 ° C, the reaction time is 4 to 6 hours, and a third mixed solution is obtained, wherein the mass ratio of the nano silicon nitride to N-(3-aminopropyl)-3-chloropropyltrimethoxysilane is 1:(0.5 to 1);

[0016] S15. The third mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 15 to 20 minutes. The separated solid is washed alternately with anhydrous ethanol and purified water for 3 times and then vacuum dried at a drying temperature of 55 to 65° C. After drying for 18 to 24 hours, the modified nano silicon nitride is obtained and ground into powder for later use.

[0017] Furthermore, the preparation method of the modified graphene comprises:

[0018] S21. The graphene powder is dissolved in N,N-dimethylformamide under stirring, and concentrated sulfuric acid is slowly added after stirring for 0.5 to 1 h, while an ice bath is performed, and the ice bath temperature is 0 to -10 ° C. After continuing to stir for 2 to 4 h, the pH value is diluted with ice water to 3 to 4 to obtain a fourth mixed solution;

[0019] S22. The fourth mixed solution was subjected to high-speed centrifugation at a speed of 10000 to 12000 rpm for 10 to 15 min, and the separated solid was washed alternately with N,N-dimethylformamide and purified water three times and then freeze-dried at a drying temperature of -20 to -40 ° C. After drying for 18 to 24 h, a graphene intermediate was obtained and ground into a powder for standby use;

[0020] S23. The graphene intermediate powder is dissolved in purified water under stirring, and propylene oxide and 0.1 mol / L sodium hydroxide solution are slowly added after stirring for 0.5 to 1 h, and the reaction temperature is set to 60 to 80 ° C. After continuing to stir the reaction for 0.5 to 1 h, ultrasonic treatment is performed at an ultrasonic frequency of 40 to 50 kHz. After ultrasonic treatment for 0.5 to 1 h, a fifth mixed solution is obtained, wherein the mass ratio of graphene to propylene oxide is 1: (3 to 5);

[0021] S24. The fifth mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 10 to 15 minutes. The separated solid is washed 5 times with purified water and then vacuum dried at a drying temperature of 50 to 60° C. After drying for 18 to 24 hours, the modified graphene is obtained and ground into powder for later use.

[0022] Furthermore, the modified graphene surface contains epoxy groups, and the nanometer size of the modified graphene layer is 80-100nm, and the specific surface area is 1800-2000m 2 / g.

[0023] Furthermore, the coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-epoxypropyltriethoxysilane, γ-chloropropyltriethoxysilane and methyltriethoxysilane.

[0024] Furthermore, the antioxidant is a compound of 2,6-di-tert-butyl-p-cresol and 3,5-di-tert-butyl-4-hydroxyphenyl phosphate, and the weight ratio of 2,6-di-tert-butyl-p-cresol to 3,5-di-tert-butyl-4-hydroxyphenyl phosphate is (1-0.5): (1-1.5).

[0025] Furthermore, the antistatic agent is one or more of cetyltrimethylammonium chloride, lauryldimethylammonium chloride, lauric acid and sodium alkylbenzene sulfonate.

[0026] Furthermore, the plasticizer is a compound of xylene dicarboxylate, dibutyl dicarboxylate and epoxidized soybean oil, and the weight ratio of xylene dicarboxylate, dibutyl dicarboxylate and epoxidized soybean oil is (1-2): (0.5-1): (0.5-1).

[0027] On the other hand, based on the same inventive concept, the present invention also provides a method for preparing a high-elastic polyethylene foam composite material, which is applied to the high-elastic polyethylene foam composite material, comprising the following steps:

[0028] S31. In a high shear mixer, low-density polyethylene, modified nano-silicon nitride, modified graphene, azodicarbonamide, a coupling agent, an antioxidant, an antistatic agent and a plasticizer are sequentially added, and the temperature is raised to 160 to 180° C., and the speed is set to 3000 to 3500 rpm after heating for 2 to 4 hours, and a molten mixture is obtained after running for 20 to 30 minutes;

[0029] S32. Under foaming conditions, the molten mixture was fed into a twin-screw extruder, the extrusion temperature was controlled to be 180 to 220 ° C, the screw speed was 100 to 150 rpm, and the desired shape was obtained according to the corresponding mold to obtain a highly elastic polyethylene foam composite intermediate;

[0030] S33. Cool and shape the high-elastic polyethylene foam composite material intermediate, cool the foamed high-elastic polyethylene foam composite material intermediate through a cooling roller, control the cooling temperature to 50-70° C., and finally cut and shape to obtain a high-elastic polyethylene foam composite material.

[0031] The mechanism of action of the above raw material components is as follows:

[0032] In the high elastic polyethylene foam composite material, low density polyethylene, modified nano silicon nitride and modified graphene work together to improve the resilience of the foam composite material through synergistic effect. Low density polyethylene is a high molecular polymer. Its molecular chain has good stretchability and plasticity during the foaming process. Its low density and flexible structure can effectively absorb impact energy, and it can quickly rebound to its original shape when the external force is removed. At the same time, low density polyethylene, as a matrix material, can provide a stable carrier support for modified nano silicon nitride and modified graphene, so that both can be evenly dispersed in low density polyethylene. Nano silicon nitride is a material with high hardness, excellent thermal stability and wear resistance. Modified nano silicon nitride is obtained by hydrogen bond cross-linking modification, so that the surface of the modified nano silicon nitride further improves the compatibility with the low-density polyethylene matrix by forming a strong hydrogen bond, so that the modified nano silicon nitride can be dispersed more evenly in the low-density polyethylene matrix, thereby improving the overall mechanical properties and thermal stability of the material. At the same time, the modified nano silicon nitride after hydrogen bond cross-linking modification can not only improve the stiffness of the foamed composite material, but also further improve the fracture toughness and impact resistance of the foamed composite material by increasing the cohesive force of the low-density polyethylene matrix, and enhance the resilience of the foamed composite material under dynamic load, so that it is not easy to cause permanent deformation when subjected to external impact. Graphene is a two-dimensional material with an ultra-high specific surface area. Modified graphene is obtained by introducing epoxy groups on the graphene surface. The modified graphene has good affinity and can be strongly chemically bonded with the low-density polyethylene matrix to optimize the molecular chain structure of polyethylene, further improving the structural stability of the foamed composite material. At the same time, through its two-dimensional structure and high specific surface area, it plays a role in stress dispersion and enhancement in the foamed composite material, avoiding stress concentration, preventing local deformation of the material, and effectively improving the resilience of the foamed composite material. At the same time, the epoxy groups on the surface of the modified graphene can react with the modified nano-silicon nitride through chemical reactions to optimize the interfacial bonding between the two, which not only further enhances the dispersibility of the modified nano-silicon nitride, but also makes the bonding between the modified graphene and the modified nano-silicon nitride more stable, avoiding the agglomeration of the two, and improving the uniformity and mechanical properties of the foamed composite material. In addition, modified graphene and modified nano-silicon nitride also synergistically improve the thermal stability of the foamed composite material. The modified nano-silicon nitride has excellent high temperature resistance, and the modified graphene has excellent thermal conductivity. When the foamed composite material is exposed to a high temperature environment, the modified graphene can effectively disperse the heat, thereby avoiding material performance degradation caused by local overheating.In short, low-density polyethylene provides a stable carrier support for modified nano-silicon nitride and modified graphene, providing basic elasticity and processability. Modified nano-silicon nitride enhances the stiffness and impact resistance of the foamed composite material, while modified graphene enhances the stress dispersion ability of the foamed composite material through its two-dimensional structure and ultra-high specific surface area. The three work together to synergistically improve the material's resilience, allowing the polyethylene foamed composite material to maintain good resilience under long-term high-load work.

[0033] Azodicarbonamide is a commonly used foaming agent that can decompose to generate gas under high temperature and certain pressure conditions, producing a foaming effect. During the foaming process, a uniform microporous structure is formed, which reduces the weight of the material and increases its elasticity and cushioning properties. This allows the foamed composite material to better recover to its original shape when impacted by external forces, thereby improving its resilience and impact resistance.

[0034] Coupling agents can improve the compatibility between polyethylene matrix and nanomaterials. When modified graphene and modified nano-silicon nitride are added to polyethylene, phase separation or agglomeration of nanomaterials will occur due to their polarity and the non-polarity of polyethylene. Coupling agents can promote the uniform dispersion of nanomaterials in the polyethylene matrix through chemical bonding, thereby enhancing the mechanical properties, thermal stability, resilience and weather resistance of the foamed composite materials.

[0035] Antioxidants can prevent polyethylene from oxidative degradation during processing. Polyethylene is prone to oxidation reaction during high-temperature processing or long-term exposure to oxygen and ultraviolet rays, which leads to molecular chain breakage and physical property degradation. The antioxidant of the present invention is a compound of 2,6-di-tert-butyl-p-cresol and 3,5-di-tert-butyl-4-hydroxyphenyl phosphate, which can improve the thermal stability of the foamed composite material, extend the service life, and maintain the excellent performance of the material by capturing free radicals and inhibiting oxidation reactions.

[0036] The antistatic agent can reduce the accumulation of static electricity on the surface of the foamed composite material, and prevent pollution, damage or safety hazards caused by static electricity. The antistatic agent of the present invention is one or more of hexadecyltrimethylammonium chloride, lignoceryldimethylammonium chloride, lauric acid and sodium alkylbenzene sulfonate, and its mechanism of action is to form a conductive network or adsorb ions on the surface of the material, thereby reducing the surface resistance and enhancing the antistatic performance of the material.

[0037] Plasticizers can improve the processability and flexibility of low-density polyethylene. The plasticizer of the present invention is a compound of xylene dicarboxylate, dibutyl dicarboxylate and epoxidized soybean oil. By inserting molecules between polyethylene molecular chains, the distance between chains is increased, the viscosity of polyethylene during processing is reduced, the interaction force between molecular chains is reduced, and the flexibility and ductility of polyethylene are increased.

[0038] (3) Beneficial effects

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. Low-density polyethylene, modified nano silicon nitride and modified graphene work through synergistic effects. Low-density polyethylene provides a stable carrier support for modified nano silicon nitride and modified graphene, and provides basic elasticity and processability;

[0041] 2. Modified nano silicon nitride improves the overall mechanical properties and thermal stability of the material, further improves the fracture toughness and impact resistance of the foamed composite material by increasing the cohesive force of the low-density polyethylene matrix, and enhances the resilience of the foamed composite material under dynamic load;

[0042] 3. Modified graphene optimizes the molecular chain structure of polyethylene, improves the structural stability of the foamed composite material, enhances the stress dispersion ability of the foamed composite material through its two-dimensional structure and ultra-high specific surface area, and prevents local deformation of the material;

[0043] 4. The modified nano silicon nitride has excellent high temperature resistance and the modified graphene has excellent thermal conductivity. The two work together to improve the thermal stability of the foamed composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a SEM image of modified nano silicon nitride in Example 1 of the present invention;

[0045] Figure 2 This is the SEM image of the modified graphene in Example 1 of the present invention. DETAILED DESCRIPTION

[0046] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] The test equipment and preparations of the embodiments described below are as follows: electronic balance (Sartorius, Germany), electric constant temperature water bath (Jiangsu Kedao), magnetic stirrer (Shanghai Meiyingpu), ultrasonic instrument (Shanghai Yixin), high-speed centrifuge (Guangzhou Jidi), vacuum drying oven (Shanghai Jiecheng), freeze dryer (Shanghai Pudong Freeze Drying), pH meter (Shanghai Yidian), high shear mixer (Nantong Fulake), twin-screw extruder (Taizhou Kedi), cooling roller (Jiangsu Jinhang), scanning electron microscope (German Zeiss), specific surface area analyzer (Beijing Best Instrument Technology), heat deformation temperature meter (Shandong Jiuxing), universal material testing machine (Suzhou Jianzhuo), Charpy impact testing machine (Shandong Dihua), rebound hardness tester (Shanghai Yaduoli); chemicals and reagents were purchased from Sigma-Aldrich.

[0048] Embodiment 1: This embodiment discloses a high elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 75 parts of low density polyethylene, 3.5 parts of modified graphene, 3 parts of azodicarbonamide, 0.75 parts of coupling agent, 0.75 parts of antioxidant, 0.3 parts of antistatic agent, and 2 parts of plasticizer. The high elastic polyethylene foam composite material also includes modified nano silicon nitride, wherein the weight ratio of the modified nano silicon nitride to the low density polyethylene is 5:75, and the modified nano silicon nitride is prepared by hydrogen bonding cross-linking modification of nano silicon nitride, and the modified nano silicon nitride has a particle size of 50 to 80 nm and a specific surface area of ​​90 to 120 m 2 / g.

[0049] In the high-elastic polyethylene foam composite material, low-density polyethylene, modified nano-silicon nitride and modified graphene work together to improve the resilience of the foam composite material through synergistic effects. Low-density polyethylene is a high-molecular polymer with a highly branched molecular chain structure. The molecules are loosely arranged and there are large space gaps, which makes the polyethylene molecular chain have good extensibility and plasticity, and the density is also low. During the foaming process, its low density and flexible structure can effectively absorb impact energy and undergo plastic deformation, but when the external force is removed, it can quickly rebound to its original shape. At the same time, as a matrix material, low-density polyethylene has a high molecular chain structure and elasticity that enables it to effectively carry nanomaterials, providing a stable carrier support for modified nano-silicon nitride and modified graphene, so that the two can be evenly dispersed in low-density polyethylene. Nano-silicon nitride is a material with high hardness, excellent thermal stability and wear resistance. Modified nano-silicon nitride is obtained by hydrogen bond cross-linking modification. Figure 1The SEM image of modified nano silicon nitride shows that the modified nano silicon nitride has a very obvious flaky structure. The surface of the modified nano silicon nitride contains a large number of nitrogen atoms. These nitrogen atoms have lone pairs of electrons and can form hydrogen bonds with hydrogen atoms in the hydrogen bond donor group. The strong hydrogen bonding effect on its surface can further improve the compatibility with the low-density polyethylene matrix, so that the modified nano silicon nitride can be dispersed more evenly in the low-density polyethylene matrix, thereby improving the overall mechanical properties and thermal stability of the material. At the same time, the modified nano silicon nitride after hydrogen bond cross-linking can not only improve the stiffness of the foamed composite material, but also further improve the fracture toughness and impact resistance of the foamed composite material by increasing the cohesive force of the low-density polyethylene matrix, and enhance the resilience of the foamed composite material under dynamic loads, so that it is not easy to undergo permanent deformation when subjected to external impact. Graphene is a two-dimensional material with an ultra-high specific surface area. Modified graphene is obtained by introducing epoxy groups (-COC-) on the graphene surface. Figure 2 The SEM image of modified graphene shows that the modified graphene has a very obvious flaky structure, with curling or irregular shapes on the edges. The modified graphene introduced with epoxy groups (-COC-) has good chemical affinity, and can be strongly chemically bonded with the low-density polyethylene matrix to optimize the molecular chain structure of polyethylene, further improving the structural stability of the foamed composite material. At the same time, the two-dimensional structure of the modified graphene gives it an extremely high specific surface area, which can effectively disperse the external stress through the thin sheet plane, thereby reducing the stress concentration phenomenon in the material, avoiding the rupture or plastic deformation of the material caused by excessive local stress, and effectively improving the resilience of the foamed composite material. At the same time, the epoxy groups on the surface of the modified graphene can react with the modified nano silicon nitride through chemical action to optimize the interface bonding force between the two, not only further enhancing the dispersibility of the modified nano silicon nitride, but also making the combination between the modified graphene and the modified nano silicon nitride more stable, avoiding the agglomeration phenomenon between the two, and improving the uniformity and mechanical properties of the foamed composite material. In addition, modified graphene and modified nano silicon nitride also synergistically improve the thermal stability of the foamed composite material. The modified nano silicon nitride has excellent high temperature resistance, and the modified graphene has excellent thermal conductivity. When the foamed composite material is exposed to a high temperature environment, the modified graphene can effectively disperse the heat, thereby avoiding the material performance degradation caused by local overheating. In short, low-density polyethylene provides a stable carrier support for modified nano silicon nitride and modified graphene, providing basic elasticity and processability. The modified nano silicon nitride enhances the stiffness and impact resistance of the foamed composite material. The modified graphene enhances the stress dispersion ability of the foamed composite material through its two-dimensional structure and ultra-high specific surface area. The three work together to synergistically improve the material's resilience, so that the polyethylene foamed composite material can still maintain good resilience under long-term high-load work.

[0050] The preparation method of the modified nano silicon nitride comprises:

[0051] S11. The nano silicon nitride powder is dissolved in anhydrous ethanol under stirring, and then ultrasonically treated at an ultrasonic frequency of 40 to 50 kHz for 0.5 to 1 h at room temperature to obtain a first mixed solution;

[0052] S12. The first mixed solution was subjected to high-speed centrifugation at a speed of 6000 to 8000 rpm for 10 to 15 min. The separated solid was washed three times with anhydrous ethanol and then vacuum dried at a drying temperature of 50 to 60 ° C. After drying for 12 to 14 h, the nano-silicon nitride intermediate was ground into a powder for standby use;

[0053] S13. Dissolve N-(3-aminopropyl)-3-chloropropyltrimethoxysilane in anhydrous ethanol under stirring, slowly add 0.1 mol / L sodium hydroxide solution after stirring for 0.5 to 1 h, and continue stirring for 2 to 3 h to obtain a second mixed solution;

[0054] S14. The nano silicon nitride intermediate powder is dissolved in the second mixed solution under stirring, the reaction temperature is set to 65 to 75 ° C, the reaction time is 4 to 6 hours, and a third mixed solution is obtained, wherein the mass ratio of the nano silicon nitride to N-(3-aminopropyl)-3-chloropropyltrimethoxysilane is 1:(0.5 to 1);

[0055] S15. The third mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 15 to 20 minutes. The separated solid is washed alternately with anhydrous ethanol and purified water for 3 times and then vacuum dried at a drying temperature of 55 to 65° C. After drying for 18 to 24 hours, the modified nano silicon nitride is obtained and ground into powder for later use.

[0056] The preparation method of the modified graphene comprises:

[0057] S21. The graphene powder is dissolved in N,N-dimethylformamide under stirring, and concentrated sulfuric acid is slowly added after stirring for 0.5 to 1 h, while an ice bath is performed, and the ice bath temperature is 0 to -10 ° C. After continuing to stir for 2 to 4 h, the pH value is diluted with ice water to 3 to 4 to obtain a fourth mixed solution;

[0058] S22. The fourth mixed solution was subjected to high-speed centrifugation at a speed of 10000 to 12000 rpm for 10 to 15 min, and the separated solid was washed alternately with N,N-dimethylformamide and purified water three times and then freeze-dried at a drying temperature of -20 to -40 ° C. After drying for 18 to 24 h, a graphene intermediate was obtained and ground into a powder for standby use;

[0059] S23. The graphene intermediate powder is dissolved in purified water under stirring, and propylene oxide and 0.1 mol / L sodium hydroxide solution are slowly added after stirring for 0.5 to 1 h, and the reaction temperature is set to 60 to 80 ° C. After continuing to stir the reaction for 0.5 to 1 h, ultrasonic treatment is performed at an ultrasonic frequency of 40 to 50 kHz. After ultrasonic treatment for 0.5 to 1 h, a fifth mixed solution is obtained, wherein the mass ratio of graphene to propylene oxide is 1: (3 to 5);

[0060] S24. The fifth mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 10 to 15 minutes. The separated solid is washed 5 times with purified water and then vacuum dried at a drying temperature of 50 to 60° C. After drying for 18 to 24 hours, the modified graphene is obtained and ground into powder for later use.

[0061] The modified graphene surface contains epoxy groups, and the nanometer size of the modified graphene layer is 80-100nm, and the specific surface area is 1800-2000m 2 / g.

[0062] The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-epoxypropyltriethoxysilane, γ-chloropropyltriethoxysilane and methyltriethoxysilane.

[0063] The antioxidant is a compound of 2,6-di-tert-butyl-p-cresol and 3,5-di-tert-butyl-4-hydroxyphenyl phosphate, and the weight ratio of 2,6-di-tert-butyl-p-cresol to 3,5-di-tert-butyl-4-hydroxyphenyl phosphate is (1-0.5): (1-1.5).

[0064] The antistatic agent is one or more of hexadecyltrimethylammonium chloride, lauryldimethylammonium chloride, lauric acid and sodium alkylbenzene sulfonate.

[0065] The plasticizer is a compound of xylene dicarboxylic acid ester, dibutyl dicarboxylic acid ester and epoxidized soybean oil, wherein the weight ratio of xylene dicarboxylic acid ester, dibutyl dicarboxylic acid ester and epoxidized soybean oil is (1-2): (0.5-1): (0.5-1).

[0066] A method for preparing a high-elastic polyethylene foam composite material, applied to the high-elastic polyethylene foam composite material, comprises the following steps:

[0067] S31. In a high shear mixer, low-density polyethylene, modified nano-silicon nitride, modified graphene, azodicarbonamide, a coupling agent, an antioxidant, an antistatic agent and a plasticizer are sequentially added, and the temperature is raised to 160 to 180° C., and the speed is set to 3000 to 3500 rpm after heating for 2 to 4 hours, and a molten mixture is obtained after running for 20 to 30 minutes;

[0068] S32. Under foaming conditions, the molten mixture was fed into a twin-screw extruder, the extrusion temperature was controlled to be 180 to 220 ° C, the screw speed was 100 to 150 rpm, and the desired shape was obtained according to the corresponding mold to obtain a highly elastic polyethylene foam composite intermediate;

[0069] S33. Cool and shape the high-elastic polyethylene foam composite material intermediate, cool the foamed high-elastic polyethylene foam composite material intermediate through a cooling roller, control the cooling temperature to 50-70° C., and finally cut and shape to obtain a high-elastic polyethylene foam composite material.

[0070] Example 2: This example discloses a high-elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 70 parts of low-density polyethylene, 2 parts of modified graphene, 2 parts of azodicarbonamide, 0.5 parts of coupling agent, 0.5 parts of antioxidant, 0.1 parts of antistatic agent, and 1 part of plasticizer. The high-elastic polyethylene foam composite material also includes modified nano silicon nitride, and the weight ratio of the modified nano silicon nitride to the low-density polyethylene is 5:70. The modified nano silicon nitride is prepared by hydrogen-bonding cross-linking modification of nano silicon nitride, and the modified nano silicon nitride has a particle size of 50 to 80 nm and a specific surface area of ​​90 to 120 m 2 / g. The preparation method of the modified nano silicon nitride and modified graphene in this embodiment is consistent with that in Example 1. The preparation method of a high elastic polyethylene foam composite material in this embodiment is consistent with that in Example 1.

[0071] Example 3: This example discloses a high-elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 80 parts of low-density polyethylene, 5 parts of modified graphene, 4 parts of azodicarbonamide, 1 part of coupling agent, 1 part of antioxidant, 0.5 part of antistatic agent, and 3 parts of plasticizer. The high-elastic polyethylene foam composite material also includes modified nano silicon nitride, and the weight ratio of the modified nano silicon nitride to the low-density polyethylene is 5:80. The modified nano silicon nitride is prepared by hydrogen-bonding cross-linking modification of nano silicon nitride, and the modified nano silicon nitride has a particle size of 50 to 80 nm and a specific surface area of ​​90 to 120 m 2 / g. The preparation method of the modified nano silicon nitride and modified graphene in this embodiment is consistent with that in Example 1. The preparation method of a high elastic polyethylene foam composite material in this embodiment is consistent with that in Example 1.

[0072] Control group 1: This embodiment differs from embodiment 1 in that modified nano silicon nitride is not contained. This embodiment discloses a high elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 75 parts of low density polyethylene, 3.5 parts of modified graphene, 3 parts of azodicarbonamide, 0.75 parts of coupling agent, 0.75 parts of antioxidant, 0.3 parts of antistatic agent, and 2 parts of plasticizer. The preparation method of the modified graphene in this embodiment is consistent with that in embodiment 1. The preparation method of a high elastic polyethylene foam composite material in this embodiment is consistent with that in embodiment 1.

[0073] Control group 2: The difference between this embodiment and embodiment 1 is that modified graphene is not contained. This embodiment discloses a high elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 75 parts of low density polyethylene, 3 parts of azodicarbonamide, 0.75 parts of coupling agent, 0.75 parts of antioxidant, 0.3 parts of antistatic agent, and 2 parts of plasticizer. The high elastic polyethylene foam composite material also includes modified nano silicon nitride, and the weight ratio of the modified nano silicon nitride to the low density polyethylene is 5:75. The modified nano silicon nitride is prepared by hydrogen bonding cross-linking modification of nano silicon nitride, and the particle size of the modified nano silicon nitride is 50-80nm, and the specific surface area is 90-120m 2 / g. The preparation method of the modified nano silicon nitride in this embodiment is consistent with that in Example 1. The preparation method of a high elastic polyethylene foam composite material in this embodiment is consistent with that in Example 1.

[0074] Control group 3: The difference between this embodiment and embodiment 1 is that azodicarbonamide is not contained. This embodiment discloses a high elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 75 parts of low density polyethylene, 3.5 parts of modified graphene, 0.75 parts of coupling agent, 0.75 parts of antioxidant, 0.3 parts of antistatic agent, and 2 parts of plasticizer. The high elastic polyethylene foam composite material also includes modified nano silicon nitride, and the weight ratio of the modified nano silicon nitride to the low density polyethylene is 5:75. The modified nano silicon nitride is prepared by hydrogen bonding cross-linking modification of nano silicon nitride, and the particle size of the modified nano silicon nitride is 50-80nm, and the specific surface area is 90-120m 2 / g. The preparation method of the modified nano silicon nitride and modified graphene in this embodiment is consistent with that in Example 1. The preparation method of a high elastic polyethylene foam composite material in this embodiment is consistent with that in Example 1.

[0075] Control group 4: The difference between this embodiment and embodiment 1 is that no coupling agent is contained. This embodiment discloses a high elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 75 parts of low density polyethylene, 3.5 parts of modified graphene, 3 parts of azodicarbonamide, 0.75 parts of antioxidant, 0.3 parts of antistatic agent, and 2 parts of plasticizer. The high elastic polyethylene foam composite material also includes modified nano silicon nitride, and the weight ratio of the modified nano silicon nitride to the low density polyethylene is 5:75. The modified nano silicon nitride is prepared by hydrogen bonding cross-linking modification of nano silicon nitride, and the particle size of the modified nano silicon nitride is 50-80nm, and the specific surface area is 90-120m 2 / g. The preparation method of the modified nano silicon nitride and modified graphene in this embodiment is consistent with that in Example 1. The preparation method of a high elastic polyethylene foam composite material in this embodiment is consistent with that in Example 1.

[0076] Control group 5: The difference between this embodiment and embodiment 1 is that no antioxidant is contained. This embodiment discloses a high elastic polyethylene foam composite material, comprising the following raw materials in parts by weight: 75 parts of low density polyethylene, 3.5 parts of modified graphene, 3 parts of azodicarbonamide, 0.75 parts of coupling agent, 0.3 parts of antistatic agent, and 2 parts of plasticizer. The high elastic polyethylene foam composite material also includes modified nano silicon nitride, and the weight ratio of the modified nano silicon nitride to the low density polyethylene is 5:75. The modified nano silicon nitride is prepared by hydrogen bonding cross-linking modification of nano silicon nitride, and the particle size of the modified nano silicon nitride is 50-80 nm, and the specific surface area is 90-120 m 2 / g. The preparation method of the modified nano silicon nitride and modified graphene in this embodiment is consistent with that in Example 1. The preparation method of a high elastic polyethylene foam composite material in this embodiment is consistent with that in Example 1.

[0077] Effect evaluation: Performance measurement of high elastic polyethylene foam composite materials: (1) Rebound performance test: The Charpy impact tester and rebound hardness tester were used to conduct the experiment, and the impact resilience and rebound rate of each experimental group of materials were recorded; (2) Tensile performance test: The materials of each experimental group were subjected to tensile test using a universal material testing machine, and the tensile strength, elastic modulus and elongation at break of each experimental group of materials were recorded; (3) Thermal stability test: The materials of each experimental group were made into thin sheets and heated at a constant pressure of 1.8 MPa. The deformation degree of the material at different temperatures was measured using a heat deformation temperature meter, and the deformation temperature of the materials of each experimental group was recorded. Three parallel tests were conducted in each experimental group, and the experimental results were averaged.

[0078] Table 1 Performance measurement results of high elastic polyethylene foam composite materials obtained in each experimental group

[0079]

[0080] Table 1 is the statistical results of the performance measurement of the high elastic polyethylene foam composite materials obtained in each experimental group. It can be seen from Table 1 that there are obvious differences in the performance of the high elastic polyethylene foam composite materials prepared in each experimental group. By comparing the performance of the high elastic polyethylene foam composite materials prepared in Examples 1 to 3 with that in Control Groups 1 to 5, it can be found that, overall, the high elastic polyethylene foam composite materials prepared in Examples 1 to 3 have better performance, and the high elastic polyethylene foam composite material prepared in Example 1 shows excellent performance, with an impact resilience of up to 90%. High impact resilience means that the material can recover quickly after being impacted, reducing the generation of permanent deformation or cracks, and the rebound rate is also up to 95%. A higher rebound rate indicates that the material can recover faster after being compressed or impacted, and the tensile strength and elastic modulus are both the largest, which means better mechanical properties, indicating that the material has excellent tolerance and fracture resistance. In addition, the heat deformation temperature is also the highest at 122.5°C. The heat deformation temperature of ordinary polyethylene is usually between 60 and 90°C. A higher heat deformation temperature indicates that the material can maintain the stability of its shape and structure at a higher temperature. By comparing Example 1 with Control Groups 1 to 2, it can be found that when modified nano-silicon nitride and modified graphene are added simultaneously when making a high-elastic polyethylene foam composite material, the overall performance of the foamed composite material can be significantly improved, and the material has excellent rebound performance and heat resistance.

[0081] Through the above limited experiments, the application effect of a high-elastic polyethylene foam composite material in Example 1 of the present invention is remarkable. By optimizing the formula of the foam composite material, modified nano silicon nitride and modified graphene are added simultaneously during the production process, and modern nanotechnology is combined to significantly improve the resilience of the polyethylene foam composite material. Low-density polyethylene provides a stable carrier support for the modified nano silicon nitride and modified graphene. The modified nano silicon nitride increases the cohesion of the low-density polyethylene matrix to improve the fracture toughness and impact resistance of the foam composite material. The modified graphene optimizes the molecular chain structure of polyethylene, and enhances the stress dispersion ability of the foam composite material through its two-dimensional structure and ultra-high specific surface area, and synergistically improves the material's resilience, so that the polyethylene foam composite material can still maintain good resilience under long-term high-load work.

[0082] Finally, it should be noted that: Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A high elastic polyethylene foam composite material, characterized in that: The invention comprises the following raw materials in parts by weight: 70 to 80 parts of low-density polyethylene, 2 to 5 parts of modified graphene, 2 to 4 parts of azodicarbonamide, 0.5 to 1 part of coupling agent, 0.5 to 1 part of antioxidant, 0.1 to 0.5 part of antistatic agent and 1 to 3 parts of plasticizer; The high elastic polyethylene foam composite material also includes: Modified nano silicon nitride; The modified nano silicon nitride and low-density polyethylene are in a weight ratio of 5: (70-80); The modified nano silicon nitride is prepared by hydrogen bonding and cross-linking modification of nano silicon nitride, and the particle size of the modified nano silicon nitride is 50 to 80 nm, and the specific surface area is 90 to 120 m 2 / g.

2. The high elastic polyethylene foam composite material according to claim 1, characterized in that: The preparation method of the modified nano silicon nitride comprises: S11. The nano silicon nitride powder is dissolved in anhydrous ethanol under stirring, and then ultrasonically treated at an ultrasonic frequency of 40 to 50 kHz for 0.5 to 1 h at room temperature to obtain a first mixed solution; S12. The first mixed solution was subjected to high-speed centrifugation at a speed of 6000 to 8000 rpm for 10 to 15 min. The separated solid was washed three times with anhydrous ethanol and then vacuum dried at a drying temperature of 50 to 60 ° C. After drying for 12 to 14 h, the nano-silicon nitride intermediate was ground into a powder for standby use; S13. Dissolve N-(3-aminopropyl)-3-chloropropyltrimethoxysilane in anhydrous ethanol under stirring, slowly add 0.1 mol / L sodium hydroxide solution after stirring for 0.5 to 1 h, and continue stirring for 2 to 3 h to obtain a second mixed solution; S14. The nano silicon nitride intermediate powder is dissolved in the second mixed solution under stirring, the reaction temperature is set to 65 to 75 ° C, the reaction time is 4 to 6 hours, and a third mixed solution is obtained, wherein the mass ratio of the nano silicon nitride to N-(3-aminopropyl)-3-chloropropyltrimethoxysilane is 1:(0.5 to 1); S15. The third mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 15 to 20 minutes. The separated solid is washed alternately with anhydrous ethanol and purified water for 3 times and then vacuum dried at a drying temperature of 55 to 65° C. After drying for 18 to 24 hours, the modified nano silicon nitride is obtained and ground into powder for later use.

3. The high elastic polyethylene foam composite material according to claim 1, characterized in that: The preparation method of the modified graphene comprises: S21. The graphene powder is dissolved in N,N-dimethylformamide under stirring, and concentrated sulfuric acid is slowly added after stirring for 0.5 to 1 h, while an ice bath is performed, and the ice bath temperature is 0 to -10 ° C. After continuing to stir for 2 to 4 h, the pH value is diluted with ice water to 3 to 4 to obtain a fourth mixed solution; S22. The fourth mixed solution was subjected to high-speed centrifugation at a speed of 10000 to 12000 rpm for 10 to 15 min, and the separated solid was washed alternately with N,N-dimethylformamide and purified water three times and then freeze-dried at a drying temperature of -20 to -40 ° C. After drying for 18 to 24 h, a graphene intermediate was obtained and ground into a powder for standby use; S23. The graphene intermediate powder is dissolved in purified water under stirring, and propylene oxide and 0.1 mol / L sodium hydroxide solution are slowly added after stirring for 0.5 to 1 h, and the reaction temperature is set to 60 to 80 ° C. After continuing to stir the reaction for 0.5 to 1 h, ultrasonic treatment is performed at an ultrasonic frequency of 40 to 50 kHz. After ultrasonic treatment for 0.5 to 1 h, a fifth mixed solution is obtained, wherein the mass ratio of graphene to propylene oxide is 1: (3 to 5); S24. The fifth mixed solution is subjected to high-speed centrifugation at a rotation speed of 10,000 to 12,000 rpm for 10 to 15 minutes. The separated solid is washed 5 times with purified water and then vacuum dried at a drying temperature of 50 to 60° C. After drying for 18 to 24 hours, the modified graphene is obtained and ground into powder for later use.

4. The high elastic polyethylene foam composite material according to claim 3, characterized in that: The modified graphene surface contains epoxy groups, and the nanometer size of the modified graphene layer is 80-100nm, and the specific surface area is 1800-2000m 2 / g.

5. The high elastic polyethylene foam composite material according to claim 1, characterized in that: The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-epoxypropyltriethoxysilane, γ-chloropropyltriethoxysilane and methyltriethoxysilane.

6. The high elastic polyethylene foam composite material according to claim 1, characterized in that: The antioxidant is a compound of 2,6-di-tert-butyl-p-cresol and 3,5-di-tert-butyl-4-hydroxyphenyl phosphate, and the weight ratio of 2,6-di-tert-butyl-p-cresol to 3,5-di-tert-butyl-4-hydroxyphenyl phosphate is (1-0.5): (1-1.5).

7. The high elastic polyethylene foam composite material according to claim 1, characterized in that: The antistatic agent is one or more of hexadecyltrimethylammonium chloride, lauryldimethylammonium chloride, lauric acid and sodium alkylbenzene sulfonate.

8. The high elastic polyethylene foam composite material according to claim 1, characterized in that: The plasticizer is a compound of xylene dicarboxylic acid ester, dibutyl dicarboxylic acid ester and epoxidized soybean oil, wherein the weight ratio of xylene dicarboxylic acid ester, dibutyl dicarboxylic acid ester and epoxidized soybean oil is (1-2): (0.5-1): (0.5-1).

9. A method for preparing a high elastic polyethylene foam composite material, used for preparing a high elastic polyethylene foam composite material as claimed in any one of claims 1 to 8, characterized in that: The method comprises the following steps: S31. In a high shear mixer, low-density polyethylene, modified nano-silicon nitride, modified graphene, azodicarbonamide, a coupling agent, an antioxidant, an antistatic agent and a plasticizer are sequentially added, and the temperature is raised to 160 to 180° C., and the speed is set to 3000 to 3500 rpm after heating for 2 to 4 hours, and a molten mixture is obtained after running for 20 to 30 minutes; S32. Under foaming conditions, the molten mixture was fed into a twin-screw extruder, the extrusion temperature was controlled to be 180 to 220 ° C, the screw speed was 100 to 150 rpm, and the desired shape was obtained according to the corresponding mold to obtain a highly elastic polyethylene foam composite intermediate; S33. Cool and shape the high-elastic polyethylene foam composite material intermediate, cool the foamed high-elastic polyethylene foam composite material intermediate through a cooling roller, control the cooling temperature to 50-70° C., and finally cut and shape to obtain a high-elastic polyethylene foam composite material.

Citation Information

Patent Citations

  • Colored high-performance and anti-static radiation cross-linked polyethylene foam material and preparation method thereof

    CN104610632A

  • Surface organic modification method for nano silicon nitride powder

    CN106543774A

  • Polyethylene foaming composition, foaming material, preparation method of composition and rotational molding polyethylene foaming product

    CN112442220A

  • Flame-retardant foam

    JP2020033519A

Cited By

  • Film containing modified graphene and preparation method thereof

    CN120966062A